Simulation of power quality events using simulink model - Tan R.H.G.; Ramachandaramurthy V.K. (2023)
This paper presents a comprehensive set of Simulink models, utilizing SimPowerSystems blockset to simulate various power quality events in distribution system. These models include distribution line fault, induction motor starting and transformer energizing models which are used to simulate various types of voltage sag. Capacitor bank switching model is also presented to simulate voltage transient at the distribution network. There are also three phase non linear load models used to simulate voltage notches and harmonic power quality events at the load side. For simplicity, these models are developed with minimum blocks and setting without scarifying the essence of power quality event. These models are also useful to simulate various power quality waveforms for power quality analysis algorithm research. These models serve as a fundamental model for analysis of complex power quality events as well as contribute to the power engineering education curriculum. 2013 IEEE.